Hybrid Porous Media Gasification of Urban Solid Waste Pre-Treated by Hydrothermal Carbonization - Diaz-Robles, L; Espinoza-Perez, A (Public Library of Science, 2023)
Global population growth and rising consumption levels have significantly increased resource use and energy demand, leading to higher greenhouse gas concentrations and increased waste output. As a result, alternative waste treatment methods for sustainable municipal solid waste (MSW) management are crucial. This research evaluates the efficiency of integrating hydrothermal carbonization (HTC) and gasification for an optimized MSW biomass blend. HTC was conducted for one hour at 220◦C in a 5 L reactor, followed by gasification in a hybrid porous medium gasifier. The study investigated the effects of different filtration speeds on combustion temperature and hydrogen concentrations. The results showed that a filtration speed of 35 cm/s resulted in a maximum combustion temperature of 1035.7◦C. The temperature remained consistent across filter speeds, while higher velocities yielded higher hydrogen concentrations. Additionally, increasing the filtration velocity raised temperatures in the hybrid bed while increasing the volumetric fraction of biomass decreased maximum temperatures. This research contributes to the understanding of merging HTC and gasification for MSW biomass blend treatment, aiming to reduce environmental impacts and costs while promoting renewable resources for long-term energy production. Copyright: © 2023 Vallejo et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.